Analysis of Sharia Banking Performance Assessment with a Balanced Scorecard Perspective in the South Tangerang City Region - Marlina, Reni; Tejawiani, Ida; Suparman; Ela, Elis (ITQAN: Journal of Islamic Economics, Management, and Finance, 2024)
This research examines whether Sharia banks in South Tangerang City can achieve good performance if measured using the Balanced Score Card (BSC) approach from the perspective of finance, customers, internal business processes, and learning and growth. This field research observes population behaviour or events in a particular area. This research is descriptive and analytical. The research results show that Bank Syariah ABC UIN Syarif Hidayatullah Branch and Bank Syariah XYZ Ciputat Branch show adequate financial health, viewed from a financial perspective showing an increase in ROI of 3.14%, while Bank Syariah in 2022. Viewed from a customer perspective, the number of savings customers at Bank Syariah ABC has decreased by 1.25%. Meanwhile, from an internal business process perspective, Bank Syariah XYZ is not considered good enough because the response time is quite long when responding to customers. Viewed from a growth and learning perspective, the performance of these two Sharia banks is in good condition.